STUDI ETNOFARMASI TUMBUHAN BERKHASIAT OBAT PADA SUKU BUTON DI KECAMATAN BINONGKO, KABUPATEN WAKATOBI, SULAWESI TENGGARA - Wa Ode Irma Indrayangingsih; Nurlina Ibrahim; Syariful Anam (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2015)
Herbal plant ethno pharmacy study in Butonse has been coducted from January to april2014 in Binongko Sub-districtm Wakatobi Regency of South East Sulawesi. This research aimed tofind out various species and plant organs used, kinds of diseases healed, and the way to use the herbalplants by Butonese in Binongko Sub-district. This was a descripive research using qualitativemethod.The sample was taken through snowball technique with 17 informans by using questiomnaire.Based on the research result, it was obtained 53 species of plants and divided into 35 families thatused as medicine.The most used plants were family of Euphorbiaceae of 6 species. It was found 3kinds of unique plants used such as tali putri, daun picah, and kayu kuda. The organs used were leaf,fruit, stem, tuber, root, rhozome. Latex, flower, stem skin, and wood skin. The most used plant’sorgan was the leaves of 56%. The wey is by boiling, pounding, chewing, squeezing, slicing, smearing,burning, dropping, soaking, consuming directly, gratting, attachng, and having smoke. The most wayused is by boiling and pounding for 34% each.